PKM-Produksi Abon Ikan Asin Jenis Kerapu (Epinephelus fuscogut-tatus) Sebagai Inovasi Olahan Berdaya Jual Tinggi - Marzuki, Ismail; Pratama, Irham; Amaliah, Fauzia; Iryani, Andi Sry; Gala, Selvina (STKIP Andi Matappa, 2021)
The purpose of this PKM is to improve the welfare of target housewives through management, production, marketing and community assistance in making shredded salted fish made from grouper fish. The method applied is in the form of production technology transfer, packaging, marketing, business financial accounting management, website creation and business partnerships with users. PKM is carried out in production houses owned by the community independently. The results of the PKM are in the form of production of shredded salted fish made from grouper by housewives with the skills and capabilities of production, marketing, and financial management that are carried out independently. The group already has marketing partners and permanent raw material sourcing partners. Their product of shredded salted grouper is named Assahra. This business has at least provided new jobs for Â± 7 housewives, including additional income for them. The conclusion from this PKM activity is that the production of shredded Assahra grouper is feasible to continue and can be managed independently by the target community, providing new work barriers, additional income and the product of shredded salted grouper is favored by consumers.